The role of human capital on foreign direct investment inflows - Karimi, Mohammad Sharif; Yusop, Zulkornain; Hook, Law Siong (Lambert Academic Publishing, 2012)
Foreign Direct Investment (FDI) and Human Capital (HC) are two areas of paramount importance to the economic growth and prosperity of any developed nation. While FDI and HC individually affect growth, they also reinforce and complement each other with varying effects. Not only have these topics been widely studied, they have also been the inspiration and focal point of two substantial bodies of literature. However, the links between these two engines of growth have been less explored. FDI inflows into developed countries over the past two decades are significantly higher than what developing countries receive and there is a huge gap between them. One of the characteristics of rich industrial economies is the availability of a workforce with a high level of HC. Whether HC has been the key driver of FDI or vice-versa is still a matter of debate.